Our only May Amelia - Holm, Jennifer L.,author (New York Scholastic, 1999)
As the only girl in a Finnish American family of seven brothers, May Amelia Jackson resents being expected to act like a lady while growing up in Washington state in 1899.
Keywords: Frontier and pioneer life -- Washington (State) -- Fiction; Brothers and sisters -- Fiction; Sex role -- Fiction; Finnish Americans -- Fiction; Washington (State) -- Fiction